FORMULATION AND CHARECTERISATION OF COLON TARGETED pH DEPENDENT MICROSPHERES OF CAPECITABINE FOR COLORECTAL CANCER - Agarwal, Dilip; Ranawat, M S; Chauhan, C S; Kamble, Ravindra (Journal of Drug Delivery and Therapeutics, 2014)
The aim of the present work was to prepare the colon-targeting microspheres of capecitabine (CPB) for the treatment of colorectal cancer to reduce dosing frequency and improve patient compliance. PH-sensitive polymer Eudragit L100, S100 separately and in combination (1:2) was used to formulate the microspheres by emulsion solvent diffusion technique using varying drug – polymer ratios (1:2 to 1:6). Microspheres were evaluated for particle size, shape, flow properties, surface morphology by scanning electron microscopy, yield, drug content, and in vitro drug release behavior and found to be significantly affected by polymer concentration. The formulated microspheres were discrete, spherical with relatively smooth surface, and with good flow properties. CPB-loaded microspheres demonstrated good entrapment efficiency (53.28 to 93.76%). The release study was done in simulated gastrointestinal fluids for 2 hrs in SGF (pH 1.2), for 3 hrs in SIF (pH 6.8) and up to 24 hrs in SCF (pH 7.4) and have shown that the drug was protected from being released in the physiological environment of the stomach and small intestine and efficiently released in colon (99.39%). Formulation ELS2 gave the best result among all formulations (1.59% release at end of 2 hrs, 19.24% at the end of 5 hr, and 99.39% at the end of the study). It is concluded from the present study that pH sensitive Eudragit microspheres are promising carriers for oral colon-targeted delivery of CPB for colorectal cancer. Key Words: Capecitabine, Eudragit L-100, Eudragit S-100, microspheres, pH sensitive, colon targeting, colorectal cancer.